Antibacterial activity of java turmeric (Curcuma xanthorrhiza Roxb.) extract against Klebsiella pneumoniae isolated from several vegetables - William Silan, Sylvester; Radu, Son; Lew, Kok Fang; Rukayadi, Yaya (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2015)
Klebsiella pneumoniae is a foodborne pathogen associated with pneumoniae. Multiresistance to antibiotics of K. pneumoniae is a significant public health treat. Recently, the use of natural products such as herbs to inhibit the growth of pathogens is increasing. Java turmeric (Curcuma xanthorrhiza Roxb.) has been reported to possess antibacterial activity against foodborne pathogens. Unfortunately, the antibacterial activity of java turmeric extract against the resistance to multiantibiotics of K. pneumoniae has not been investigated. In this study, the antibacterial activity of Java turmeric extract was tested against 24 isolates of resistant K. pneumoniae that was isolated from several vegetables; lettuce, cucumber, tomato and carrot, using the methods recommended by the Clinical and Laboratory Standard Institute (CSLI), including disc diffusion method, minimal inhibitory concentration (MIC), minimal bactericidal concentration (MBC) and killing time at concentration 0× MIC, 1/2× MIC, 1× MIC, 2× MIC and 4× MIC with predetermined time of 0, 0.25 , 0.5, 1, 2 and 4 h. The results showed that Java turmeric extract is susceptible to all resistant K. pneumoniae with inhibition zones ranging from 8.67 ± 0.58 to 10.00 ± 0.00 mm. The MIC and MBC values for the K. pneumoniae isolates against all bacterial isolates was 1.25 and 2.5 mg/ml, respectively. The killing time curve shows the reduction of resistant K. pneumoniae cells is fast acting; > 3 log10 within less than 15 min at 4× MIC (5.0 mg/ml). Finally, the isolates were completely killed at 4× MIC for 15 min. In conclusion, the Java turmeric extracts can be developed as natural antimicrobial agent to inhibit the growth of K. pneumoniae in food system.